Integrating management of marine activities in Australia - Robert L. Stephenson; Alistair J. Hobday; Ian Butler; Toni Cannard; Mel Cowlishaw; Ian Cresswell; Christopher Cvitanovic; Jon C. Day; Kirstin Dobbs; Leo X.C. Dutra; Stewart Frusher; Maree Fudge; et al. (Ocean & Coastal Management, 2023)

Genomic evidence of geographically widespread effect of gene flow from polar bears into brown bears - James A. Cahill; Ian Stirling; Logan Kistler; Rauf Salamzade; Erik Ersmark; Tara L. Fulton; Mathias Stiller; Richard E. Green; Beth Shapiro (Molecular Ecology, 2015)
Polar bears are an arctic, marine adapted species that is closely related to brown bears. Genome analyses have shown that polar bears are distinct and genetically homogeneous in comparison to brown bears. However, these analyses have also revealed a remarkable episode of polar bear gene flow into the population of brown bears that colonized the Admiralty, Baranof and Chichagof islands ( ABC islands) of Alaska. Here, we present an analysis of data from a large panel of polar bear and brown bear genomes that includes brown bears from the ABC islands, the Alaskan mainland and Europe. Our results provide clear evidence that gene flow between the two species had a geographically wide impact, with polar bear DNA found within the genomes of brown bears living both on the ABC islands and in the Alaskan mainland. Intriguingly, while brown bear genomes contain up to 8.8% polar bear ancestry, polar bear genomes appear to be devoid of brown bear ancestry, suggesting the presence of a barrier to gene flow in that direction.

Ancient DNA supports southern survival of R ichardson's collared lemming ( D icrostonyx richardsoni ) during the last glacial maximum - Tara L. Fulton; Ryan W. Norris; Russell W. Graham; Holmes A. Semken; Beth Shapiro (Molecular Ecology, 2013)
Collared lemmings (genus D icrostonyx ) are circumpolar A rctic arvicoline rodents associated with tundra. However, during the last glacial maximum ( LGM ), D icrostonyx lived along the southern ice margin of the L aurentide ice sheet in communities comprising both temperate and boreal species. To better understand these communities and the fate of these southern individuals, we compare mitochondrial cytochrome b sequence data from three LGM ‐age D icrostonyx fossils from south of the L aurentide ice sheet to sequences from modern Dicrostonyx sampled from across their present‐day range. We test whether the D icrostonyx populations from LGM ‐age continental USA became extinct at the P leistocene– H olocene transition ~11000 years ago or, alternatively, if they belong to an extant species whose habitat preferences can be used to infer the palaeoclimate along the glacial margin. Our results indicate that LGM ‐age D icrostonyx from I owa and S outh D akota belong to D icrostonyx richardsoni , which currently lives in a temperate tundra environment west of Hudson Bay, Canada. This suggests a palaeoclimate south of the Laurentide ice sheet that contains elements similar to the more temperate shrub tundra characteristic of extant D . richardsoni habitat, rather than the very cold, dry tundra of the N orthern A rctic. While more data are required to determine whether or not the LGM southern population is ancestral to extant D . richardsoni , it seems most probable that the species survived the LGM in a southern refugium.

Reproductive and menstrual factors and mammographic density in African American, Caribbean, and white women - Parisa Tehranifar; Diane Reynolds; Julie Flom; Loralee Fulton; Yuyan Liao; Elizabeth Kudadjie-Gyamfi; Mary Beth Terry (Cancer Causes & Control, 2011)